EXPLORING FUTURE BIOLOGY TEACHERS’ LITERACY: A PATHWAY TO CONTEXTUAL CURRICULUM INNOVATION IN ARCHIPELAGIC EDUCATION - Sendy Putra Pradana; Advend Sri Rizki Sianturi; Muhammad Khoirul Antony; Ahmad Naharuddin Ramadhan (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
The development of students’ scientific competence is closely tied to the literacy skills of those who teach them. Consequently, pre-service teachers’ mastery of biotechnology concepts becomes a key foundation for nurturing scientific literacy in future classrooms. This study aims to describe the biotechnology literacy profile of pre-service biology teachers regarding both conventional and modern biotechnology within the context of the Maluku Archipelago. Employing a quantitative descriptive approach, the research involved 20 students enrolled in the Biology Education Program at Pattimura University. The instrument, in the form of open-ended tests, was developed based on three dimensions of biotechnology literacy (conceptual, procedural, and socio-scientific) adapted to the local insular context. Data were analyzed using descriptive statistics to classify levels of competence. The findings revealed that the overall level of biotechnology literacy among participants was categorized as good (mean score = 72.88), with the highest achievement in conceptual literacy (86.25%), followed by procedural (70.31%) and socio-scientific literacy (68.75%). These results indicate that while the understanding of fundamental biotechnological concepts is relatively strong, the application and reflective competencies related to social, ethical, and environmental issues require further reinforcement. The study recommends the integration of coastal local contexts, authentic project-based practices, and socio-scientific issue training to enhance the biotechnology literacy of pre-service teachers in island regions.